Depression screening and education: an examination of mental health literacy and stigma in a sample of Hispanic women - Veronica Lopez; Katherine Sanchez; Michael O. Killian; Brittany H. Eghaneyan (BMC, 2018)
Abstract Background Mental health literacy consists of knowledge of a mental disorder and of the associated stigma. Barriers to depression treatment among Hispanic populations include persistent stigma which is primarily perpetuated by inadequate disease literacy and cultural factors. U.S.-born Hispanics are more likely to have depression compared to Hispanics born in Latin America and are less likely to follow a treatment plan compared to non-Hispanic whites. Hispanic women are more likely to access treatment through a primary care provider, making it an ideal setting for early mental health interventions. Methods Baseline data from 319 female Hispanic patients enrolled in Project DESEO: Depression Screening and Education: Options to Reduce Barriers to Treatment, were examined. The study implemented universal screening with a self-report depression screening tool (the 9-item Patient Health Questionnaire (PHQ-9) and took place at one federally qualified health center (FQHC) over a 24-month period. The current analysis examined the relationship between four culturally adapted stigma measures and depression knowledge, and tested whether mental health literacy was comparable across education levels in a sample of Hispanic women diagnosed with depression. Results Almost two-thirds of the sample had less than a high school education. Depression knowledge scores were significantly, weakly correlated with each the Stigma Concerns About Mental Health Care (ρ = − .165, p = .003), Latino Scale for Antidepressant Stigma (p = .124, p = .028), and Social Distance scores (p = .150, p = .007). Depression knowledge (F[2, 312] = 11.82, p < .001, partial η 2 = .071), Social Distance scores (F[2, 312] = 3.34, p = .037, partial η 2 = .021), and antidepressant medication stigma scores (F[2, 312] = 3.33, p = .037, partial η 2 = .015) significantly varied by education category. Participants with at least some college education reported significantly greater depression knowledge and less stigma surrounding depression and medication than participants with lower education levels. Conclusions Primary care settings are often the gateway to identifying undiagnosed mental health disorders, particularly for Hispanic women with comorbid physical health conditions. This study is unique in that it aims to examine the specific role of patient education level as a predictor of mental health literacy. For Hispanic women, understanding the mental health literacy of patients in a healthcare setting may improve quality of care through early detection of symptoms, culturally effective education and subsequent engagement in treatment. Trial registration The study was registered with https://clinicaltrials.gov/: NCT02491034 July 2, 2015.